Neutron Star Kicks plus Rockets as a Mechanism for Forming Wide Low-eccentricity Neutron Star Binaries - Ryosuke Hirai; Philipp Podsiadlowski; Alexander Heger; Hiroki Nagakura (The Astrophysical Journal Letters, 2024)
Recent neutron star surface observations corroborate a long-standing theory that neutron stars may be accelerated over extended periods after their birth. We analyze how these prolonged rocket-like accelerations, combined with rapid birth kicks, impact binary orbits. We find that even a small contribution of rocket kicks combined with instantaneous natal kicks can allow binaries to reach period–eccentricity combinations unattainable in standard binary evolution models. We propose these kick + rocket combinations as a new channel to form wide low-eccentricity neutron star binaries such as Gaia NS1, as well as inducing stellar mergers months to years after a supernova to cause peculiar high-energy transients.